Optimal Sizing of Battery Energy Storage System in a Shipboard Power System with considering Energy Management Optimization - Xianqiang Bao; Xinghua Xu; Yan Zhang; Yiyong Xiong; Chengya Shang (Discrete Dynamics in Nature and Society)
Due to the increasing concerns about the environmental and economic issues of traditional ships, all-electric ships with energy storage and renewable energy integration have become more and more appealing for the forthcoming future. In this paper, an optimal energy storage system (ESS) capacity determination method for a marine ferry ship is proposed; this ship has diesel generators and PV panels. ESSs sizing optimization and power system scheduling optimization are simultaneously conducted and it is converted to a mixed-integer quadratic programming (MIQP) model with special modeling techniques. The case study shows that the proposed method is flexible and effective, and the relationships between the ESSs size and the discharge rate, life cycle times, or initial investment cost are investigated.